Functional properties and storage stability of optimized cereal-based complementary foods - Saidu Yusuf; Suleiman Ahmed Isa; Jubrin Baba; Turaki Abdullahi Aliyu; Yusuf Abdulrahman Bashir (Croatian Journal of Food Science and Technology, 2022)
The functional properties and good quality of food materials are important factors that determine the suitability for complementary foods for children. This study evaluated the functional properties and storage stability of cereal-based and legume- based complementary food (CF). Nutri-survey (2007) was used to optimize and generate six composite blends designated F1, F2, F3, F4, F5, and F6 from yellow maize (Zea mays), wheat (Triticum aestivum), millet (Pennisetumglaucum), groundnut (Arachis hypogea), soyabeans (Glycine max), and Moringa oleifera. Freshly prepared samples were subjected to analysis of functional properties. During storage, the composite blends were subjected to sensory evaluation, microbial count, moisture content, peroxide value and free fatty acid determination at 15-day intervals for a period of 60 days. Data obtained were analyzed by ANOVA and results expressed as mean and standard error of mean. Results of functional properties revealed that bulk density ranged from (0.63-0.81 g/cm3), water absorption capacity (86-90%), swelling index (0.33-1.34 cm3/g), reconstitution index (2.20-3.20) and pH (6.52-6.69). The organoleptic properties and keeping quality of the formulated complementary foods were not signiﬁcantly different (P> 0.05) at baseline and end line. Therefore, this study provides a basis for the development of acceptable complementary foods with optimal functional properties and storage stability.